IGF‐1‐mediated osteoblastic niche expansion enhances long‐term hematopoietic stem cell engraftment after murine bone marrow transplantation. (28th October 2013) - Caselli, Anna; Olson, Timothy S.; Otsuru, Satoru; Chen, Xiaohua; Hofmann, Ted J.; Nah, Hyun‐Duck; Grisendi, Giulia; Paolucci, Paolo; Dominici, Massimo; Horwitz, Edwin M.
Abstract: The efficiency of hematopoietic stem cell (HSC) engraftment after bone marrow (BM) transplantation depends largely on the capacity of the marrow microenvironment to accept the transplanted cells. While radioablation of BM damages osteoblastic stem cell niches, little is known about their restoration and mechanisms governing their receptivity to engraft transplanted HSCs. We previously reported rapid restoration and profound expansion of the marrow endosteal microenvironment in response to marrow radioablation. Here, we show that this reorganization represents proliferation of mature endosteal osteoblasts which seem to arise from a small subset of high‐proliferative, relatively radio‐resistant endosteal cells. Multiple layers of osteoblasts form along the endosteal surface within 48 hours after total body irradiation, concomitant with a peak in marrow cytokine expression. This niche reorganization fosters homing of the transplanted hematopoietic cells to the host marrow space and engraftment of long‐term‐HSC. Inhibition of insulin‐like growth factor (IGF)‐1‐receptor tyrosine kinase signaling abrogates endosteal osteoblast proliferation and donor HSC engraftment, suggesting that the cytokine IGF‐1 is a crucial mediator of endosteal niche reorganization and consequently donor HSC engraftment. Further understanding of this novel mechanism of IGF‐1‐dependent osteoblastic niche expansion and HSC engraftment may yield clinical applications for improving engraftment efficiency after clinical HSC transplantation. Stem Cells 2013;31:2193–2204